Effect of Structured Physical Exercise on Sleep Quality in Third Trimester Pregnant Women - Hasnia (Bulletin of Inspiring Developments and Achievements in Midwifery, 2024)
Poor sleep quality is common among pregnant women, particularly in the third trimester, and may negatively affect maternal and fetal health. An initial survey conducted at the Ambacang Health Center revealed that 65% of pregnant women experienced sleep disturbances. This study aimed to examine the effect of structured physical exercise on sleep quality in third trimester pregnant women. A quasi-experimental study with a pretest–posttest design was conducted involving 20 third trimester pregnant women selected through purposive sampling in the working area of the Ambacang Health Center. The intervention consisted of structured physical exercise performed for three weeks, with a frequency of three sessions per week. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. The results demonstrated a significant improvement in sleep quality following the structured physical exercise intervention (p < 0.05). Most participants also reported feeling more refreshed and energized after participating in the exercise program. These findings indicate that structured physical exercise is an effective non-pharmacological intervention to improve sleep quality and reduce sleep disturbances in third trimester pregnant women. Therefore, structured physical exercise should be considered as part of routine prenatal care programs to enhance maternal well-being during pregnancy.